P69. High-frequency (>500 Hz) recordings from deep brain macroelectrodes reveal local interactions of subcortical multi-unit activity. Issue 8 (August 2018) - Waterstraat, G.; Kühn, A.; Curio, G.
Abstract : Introduction: While low-frequency local field potentials (LFPs) are generated mainly by postsynaptic potentials, high-frequency (hf-) LFP-activity (>500 Hz) is thought to be a correlate of multi-unit spiking activity. Here, we explore hf-recordings from electrodes implanted for deep brain stimulation for the presence of local interactions of multi-unit activity. Methods: LFPs were recorded postoperatively after implantation of deep brain stimulation electrodes (each featuring 4 linearly arranged contacts) in 2 patients (#1: globus pallidus internus for multisegmental dystonia; #2: subthalamic nucleus for Parkinson's disease) using a dedicated low-noise signal amplifier at a sampling rate of 10 kHz. Imaginary part of coherency was calculated between electrodes as a measure of true brain interactions without interference from volume conduction effects. To rule out competing technical and biological mechanisms, the analysis was repeated on recordings from a dummy head and, resp., on surface-EMG recordings. Results: The power spectral density of the recordings significantly deviated from a 1/f-characteristic exhibiting a plateau at 150–2.000 Hz. Moreover, at frequencies >500 Hz, imaginary part of coherency indicated the presence of 'true' interactions between neighboring pairs of bipolar chain derivations. These signal characteristics were neither present in the dummy-head recordings nor in the surface-EMG recordings. Discussion and significance: LFP recordings from two different subcortical sites and in two different diseases indicated the detectability of locally interacting multi-unit activity using macroelectrodes. Major competing mechanisms could be ruled out in control measurements. Further recordings will address the general consistency of these findings and explore potential correlations with clinical data. Acknowledgement: This work was supported byKFO 247 (DFG grant Ni1308/1-2 ).